First Report of Powdery Mildew Caused by Erysiphe polygoni on Trifolium repens in China - Zhang, Zikun (Plant disease, 2022)
White clover (Trifolium repens L.) belongs to the Fabaceae family legume and is cultivated in China for its medicinal properties and ornamental value. White clover is grown around the world for forage, turf , green manure and soil conservation purposes (Zhang el al. 2016). In October 2021, an investigation of a 1,000 m2 plant nursery in Lanzhou, China (36°06'N, 103°83'E) found that 80% of White clover plants were infected, and powdery mildew covered 95% of the leaf area. The disease had seriously destroyed the forage quality and reduced the ornamental value. Initially, thin, radial, irregular white colonies appeared on leaves and gradually spread to stems. The white colonies then expanded and thickened to cover upper surface of the leaf, and microscopic hyphae appeared on the bottom of the leaf. In severe cases, the infection resulted in dieback of the leaf. A small area of sporulating fungus was stripped off from the leaf surface with tape and mounted in sterile water for microscopic examination (Mukhtar et al. 2017). Conidiophores were cylindrical, consisting of a foot cell followed by three to four short cells, measuring 75 to 160 × 7 to 10 μm. Conidiophores had straight, cylindric foot cells ranging from 25 to 40 µm long. Singly produced conidia were hyaline and ranged in shape from oblong to cylindrical. Conidia lacked distinct fibrotic bodies and measured 30 to 45 × 15 to 25 μm in length. Long, unbranched germ tubes formed from the ends of the conidia and nipple-shaped appressoria developed on epiphytic mycelia. Based on these morphological characteristics, the pathogen was initially identified morphologically as Erysiphe polygoni (Braun and Cook 2012). To validate the identity, the internal transcribed spacer (ITS) region of the pathogen (SY77) rDNA was amplified by PCR and sequenced using the ITS1/ITS4 primers (White et al. 1990). The resulting sequences were registered to GenBank (GenBank Accession No.OM280998). The ITS sequence of the SY77 was 100% (640/640) identical to E. polygoni (LC009892) on Polygonum aviculare in the United Kingdom and 99% (638/640) identical to E. polygoni (MK685172) on Antigonon leptopus in Taiwan. MEGA 7.0 was used to conduct the neighbor-joining phylogenetic analysis using the ITS sequences from GenBank. The data indicated that the strain SY77 and E. polygoni clustered together on the same branch. Pathogenicity tests were conducted by gently pressing the infected leaves onto five healthy potted White clover plants, while five non-inoculated plants were used as controls (Michael et al. 2021). The plants were maintained in a growth chamber (25 ℃, 14 h light, and 10 h dark period, RH > 80%). After 10 days, the inoculated plants developed powdery mildew symptoms, whereas the control plants remained symptom-free. The fungus on the inoculated plants was re-isolated, re-identified, and confirmed as E. polygoni based on morphological observations and molecular identification. There is no previous report on E. polygoni causing powdery mildew on White clover in China. The powdery mildew caused by E. polygoni on Red clover has been reported in China and Bulgaria, respectively (Yuan el al.1991; Galina el al. 2017). To our knowledge, this is the first report of powdery mildew caused by E. polygoni on White clover in China. References: 1. Zheng, L., et al. 2018. Plant Dis. 102:628. 2. Mukhtar, G., et al. 2017. Plant Dis.101:1, 246. 3. Braun, U., and Cook, R. T. A. 2012. Taxonomic Manual of the Erysiphales (Powdery Mildews), CBS Biodiversity Series No.11. CBS, Utrecht. 4. Michael, R. F., et al. 2021.Plant Dis. First look.( doi.org/ 10.1094/PDIS-09-21-2060-PDN). 5. Yuan, Q. H., el al.1991. Pratacult Sci.05:59 (in Chinese). 6. Galina, N., et al, 2017. BIOTECHNOL Anim Husb.33.127